Study of Herbal Product Sales form A Digital Marketing Perspective (Case Study of PT Ebliethos Digital Indonesia) - Ulfah, Indar Fauziah; Haspitasari, Selvia (Jurnal Bisnis, Manajemen, dan Ekonomi, 2024)
Currently, selling herbal products has become an alternative for the public due to their low price, known efficacious compositions, and availability in several marketplaces without needing a doctor's prescription. This research aims to explain the digital marketing mechanism for selling herbal products at PT Ebliethos Digital Indonesia. The study was conducted to understand the impact of digital marketing on sales of herbal products at PT Ebliethos Digital Indonesia. The research method used in this case study is descriptive qualitative, describing the discussion based on the problem formulation in research, drawing from scientific studies sourced from company data, books, journals, and other scientific media. The research results indicate that digital marketing is the best alternative for companies; it helps reach a broader target market, ensures safer product sales, and reduces expenses and operational costs. This safety and cost-effectiveness of digital marketing in selling herbal products positively impacts the company, leading to an increase in turnover from year to year